Zapleti v času rehabilitacije po zlomih v predelu kolka in njihova povezanost z izidom rehabilitacije - Ivanovski, Matic (Rehabilitacija (Ljubljana), 2017)
Background: Hip fracture is a common injury among older population. It is closely related to osteoporosis and falls. The rehabilitation goal is to return the patients% functioning to pre-fracture state. Factors that influence recovery during initial treatment and comprehensive rehabilitation include comorbidities and complications. The objective of our paper was to find out which comorbidities are common among patients with hip fracture, which complications occur during rehabilitation and if there is a correlation with the outcome of comprehensive rehabilitation. Methods: Data on comorbidities and complications were analysed for 97 patients after hip fracture admitted to comprehensive inpatient rehabilitation between May 2013 and May 2015. Rehabilitation outcome was evaluated with the Functional Independence Measure (FIM). Motor FIM subscale results and rehabilitation duration were used to calculate two measures of complex rehabilitation outcome: progress and efficiency. We used Pearson%s correlation to evaluate association of comorbidities, number of complications and motor FIM scores. Results: The patients achieved clinically important progress. Correlation between number of comorbidities and number of complications was positive and statistically significant, but low (r=0.33, p=0.001). Efficiency of complex rehabilitation was statistically significantly negatively associated with number of complications (p=0.011), but the correlation was low (r=-0.26). Conclusions: Patients after hip fracture achieve important progress during complex inpatient rehabilitation. Complications decrease rehabilitation efficiency.
Keywords: comorbidities; complications; efficiency; hip fracture; Hip Fractures; izid; outcome; rehabilitacija; Rehabilitation; spremljajoče bolezni; učinkovitost; vocational rehabilitation; zapleti; zlom kolka